Is Tiger Woods Loss Averse? Persistent Bias in the Face of Experience, Competition, and High Stakes - Pope, Devin G; Schweitzer, Maurice E (American Economic Review, 2011)
Although experimental studies have documented systematic decision errors, many leading scholars believe that experience, competition, and large stakes will reliably extinguish biases. We test for the presence of a fundamental bias, loss aversion, in a high-stakes context: professional golfers' performance on the PGA Tour. Golf provides a natural setting to test for loss aversion because golfers are rewarded for the total number of strokes they take during a tournament, yet each individual hole has a salient reference point, par. We analyze over 2.5 million putts using precise laser measurements and find evidence that even the best golfers—including Tiger Woods—show evidence of loss aversion. (JEL D03, D81, L83).